Rapidly-cured light-cured pit and fissure sealing agent material and preparation method thereof
By using a combination of resin matrix material, diluent, inorganic filler, photocuring initiator and anti-hydrolytic agent in the photocuring hole-trench sealing agent material, and using heating and water removal treatment and vacuum centrifugal stirring, the problem of incomplete polymerization shrinkage and polymerization during the material curing process is solved, and higher curing strength, compressive strength and adhesion are achieved, thereby improving the anti-carious effect and biosafety.
Patent Information
- Application Number
- CN202411223280.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-02-28
AI Technical Summary
The existing photocuring hole-trench sealing agent materials have problems such as polymerization shrinkage and incomplete polymerization during the curing process, resulting in unsatisfactory curing strength, affecting compressive strength and adhesion, and thus affecting the anti-carious effect.
The combination of resin matrix material, diluent, inorganic filler, photocuring initiator and anti-hydrolyzer is adopted, and a fast-curing photocuring groove sealing agent material is formed through heating and water removal treatment and vacuum centrifugal stirring.
It significantly improves the curing strength, compressive strength and adhesiveness of the material, shortens the curing time, extends the shelf life, and enhances the anti-caries effect and biosafety.
Smart Images

Figure CN119523814A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pit and fissure sealing materials, in particular to a fast-curing light-curing pit and fissure sealant material and a preparation method thereof. Background Art
[0002] Dental caries is one of the most common diseases in humans, and occlusal pit and fissure caries account for 90% of dental caries. The incidence of dental caries in children in my country is relatively high. The prevalence of deciduous teeth in 5-year-old children has reached 70.9%, far exceeding the prevalence of permanent teeth in 12-year-old children (34.5%). Dental caries is one of the most common oral diseases in children, which seriously harms the growth and development of children's oral and maxillofacial system. Pit and fissure sealants are recognized as an effective method to prevent pit and fissure caries. Therefore, exploring appropriate methods is of great significance for the prevention and treatment of deciduous tooth caries. Pit and fissure sealants are also called pit and fissure sealants, also known as anti-caries coatings. They are a new type of oral medical polymer material developed in the 1960s. Applying it to the pits and fissures on the tooth surface, it forms a barrier after curing, which can effectively seal the pits and fissures and isolate the caries-causing factors in the oral environment from invading the teeth, thereby preventing the occurrence of dental caries. Pit and fissure sealants are recognized as safe anti-caries materials with great practicality. Currently, pit and fissure sealant technology has been widely used in the prevention of caries in young permanent teeth in my country and other countries around the world. Most economically developed cities have launched government-led and funded pit and fissure sealing projects for sixth-year teeth.
[0003] Pit and fissure sealant materials have been developed to date. The basic components of the materials can be divided into glass ionomers, resin-modified glass ionomers, and resin pit and fissure sealants. There are many types of pit and fissure sealants. Most materials have poor curing strength due to factors such as polymerization shrinkage and incomplete polymerization, which affects the compressive strength and adhesion of the materials, thereby affecting the curing time of the materials, and thus affecting the safety of the materials and the effectiveness of preventing caries. The main components of light-cured pit and fissure sealants are generally composed of synthetic organic polymer resin matrix, diluent, initiator, colorant, and inorganic filler components. Bis-GMA-based resin material is a widely used resin material. The resin material will produce polymerization shrinkage during curing, which will cause a small gap between the cured sealant and the tooth tissue, allowing bacteria and liquids in the oral cavity to penetrate into the interior of the sealant or below it, causing microleakage and affecting the sealing effect. At the same time, when the resin-based pit and fissure sealant is cured, some monomers may not be completely polymerized and remain in the resin. These unpolymerized monomers may dissolve from the resin and then be released into the oral cavity, causing potential biosafety hazards to the human body. Other components of light-cured pit and fissure sealants, such as inorganic fillers and diluents, will also absorb moisture from the environment, thus affecting its curing time. The polymerization mode of the light-curing lamp is one of the factors that affect the marginal permeability of the pit and fissure sealant. Light curing is a key step in the application process of composite resin restoration. It can be cured by irradiating light of a certain wavelength for 20 to 40 seconds. The success of the composite material depends on the transmission of sufficient light energy to the resin to achieve sufficient polymerization. Therefore, at the current stage when resin materials and light-curing equipment are constantly changing, according to the anatomical and physiological characteristics of young permanent teeth, the selection of pit and fissure sealant materials that can reduce microleakage, increase material curing time and material storage time, and use more convenient and quick operation methods to improve the effectiveness of pit and fissure sealing technology have guiding significance for clinical practice.
[0004] However, light-curing pit and fissure sealant materials with excellent curing time effect have always been one of the major challenges in preventing the occurrence of caries. As a result, the demand for material screening and improvement of production methods of light-curing pit and fissure sealant materials has remained high. Efficient and good material preparation and processing methods are still the focus of current research, and the problem of shortening the curing time is still the main obstacle of light-curing pit and fissure sealant materials. Although the current light-curing pit and fissure sealant materials have satisfactory compressive strength and other excellent properties, the various materials are uneven, and the various preparation methods are significantly different. The materials still have polymerization shrinkage, incomplete polymerization and other phenomena, which affect the compressive strength and curing efficiency of the materials, thereby affecting the safety of the materials and the effectiveness of preventing caries. Summary of the invention
[0005] In order to solve the deficiencies in the prior art, the present invention provides a fast-curing light-curing pit and fissure sealant material and a preparation method thereof, which improve the curing efficiency, compression resistance and adhesion of the light-curing pit and fissure sealant material.
[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0007] A fast-curing light-curing pit and fissure sealant material comprises the following components: a resin matrix material, a diluent, an inorganic filler, a light-curing initiator and an anti-hydrolysis agent.
[0008] Preferably, a fast-curing light-curing pit and fissure sealant material comprises the following components, measured by mass percentage: 20% to 90% of a resin matrix material, 5% to 45% of a diluent, 1% to 30% of an inorganic filler, 0.1% to 10% of a light-curing initiator, and 0.5% to 15% of an anti-hydrolysis agent, and the total content of each component is 100%.
[0009] More preferably, a fast-curing light-curing pit and fissure sealant material comprises the following components, calculated by mass percentage: 45% to 70% of a resin matrix material, 15% to 30% of a diluent, 5% to 20% of an inorganic filler, 0.5% to 5% of a light-curing initiator, and 0.5% to 10% of an anti-hydrolysis agent, and the total content of each component is 100%.
[0010] Exemplarily, the mass percentages of the resin matrix material, the diluent, the inorganic filler, the photocuring initiator, and the anti-hydrolysis agent are 63%, 24.5%, 10%, 1%, and 1.5%, respectively.
[0011] Exemplarily, the mass percentages of the resin matrix material, the diluent, the inorganic filler, the photocuring initiator, and the anti-hydrolysis agent are 57.8%, 22%, 18%, 1.3%, and 0.9%, respectively.
[0012] Preferably, the inorganic filler is an inorganic filler that has been subjected to a heating and dehydration treatment.
[0013] Preferably, the resin matrix material includes one or both of bisphenol A-glycidyl methacrylate (Bis-GMA) and diurethane dimethacrylate (UDMA) in any proportion.
[0014] Preferably, the diluent includes methyl methacrylate, triethylene glycol dimethacrylate (TEGDMA), or a mixture of the two in any proportion.
[0015] Preferably, the inorganic filler includes one or more of silicon dioxide, aluminum oxide, glass powder, hydroxyapatite, diatomaceous earth, and barium silicate mixed in any proportion;
[0016] Preferably, the photocuring initiator is a CQ visible light initiation reaction system, which is a mixture of at least one or more of camphorquinone, pentaerythritol tetrakis-3-mercaptopropionate (PETMP) and n-dodecyl mercaptan in any proportion.
[0017] Preferably, the anti-hydrolysis agent is at least one or more of monomeric carbodiimide, polymeric carbodiimide, diphenyliodonium hexafluorophosphate, isocyanate anti-hydrolysis agent, oxazoline compound, and epoxy compound mixed in any proportion.
[0018] Preferably, in the components of a fast-curing light-curing pit and fissure sealant material, the resin matrix material is bisphenol A-glycidyl methacrylate, the diluent is triethylene glycol dimethacrylate, the light-curing initiator is camphorquinone, the anti-hydrolysis agent is diphenyliodonium hexafluorophosphate, and the inorganic filler is one or more of silicon dioxide, glass powder, diatomaceous earth, and barium silicate mixed in any proportion. More preferably, the inorganic filler is a mixture of silicon dioxide and diatomaceous earth.
[0019] Preferably, the content of the inorganic filler passing through a 300-400 mesh sieve (38-50 μm) is not less than 85%.
[0020] The present invention also provides a method for preparing a fast-curing light-curing pit and fissure sealant material, comprising the following steps:
[0021] In a light-proof condition, the inorganic filler and the resin matrix material are heated to remove water, and the resin matrix material is heated to a molten state;
[0022] Under light-proof conditions, the diluent, photocuring initiator, anti-hydrolysis agent, dehydrated inorganic filler and molten resin matrix material are mixed and stirred to form a homogeneous viscous liquid, which is then stirred by vacuum centrifugation to obtain a photocurable pit and fissure sealant material.
[0023] The vacuum centrifugal stirring time is 5 minutes, and the centrifugal speed is sequentially set to 900 r / min for the starting speed of 0-10S, 1000 r / min for 10-100S, 1300 r / min for 100-270S, and 900 r / min for the speed reduction of 270-300S.
[0024] The temperature for heating and dehydrating the inorganic filler and the resin matrix material is 50°C to 70°C.
[0025] The inorganic filler and the resin matrix material are heated and dehydrated in a light-proof vacuum drying oven.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention combines resin matrix / diluent / photocuring initiator / anti-hydrolysis agent / inorganic filler components in a photocurable pit and fissure sealant material. The addition of the anti-hydrolysis agent ensures that the photocurable pit and fissure sealant material has anti-hydrolysis ability on a certain basis, can significantly improve the hydrolysis resistance of the material, and prolong the shelf life; at the same time, the curing strength, compressive strength and strong bonding force of the photocurable pit and fissure sealant material can be improved, and the curing time can be reduced, which has a promoting effect on improving the effect of clinical sealing, and improves the biological safety of the material and the effectiveness of clinical sealing; the present invention heats and dries the raw material for a certain period of time to remove water, so as to remove the hydrolysis caused by the unstable absorption of moisture in the environment by the raw material itself, or the penetration of various enzymes and bacteria in the environment into the polymer, which affects the curing strength; the photocurable pit and fissure sealant material of the present invention is formed after being irradiated by a light curing lamp to obtain a photocurable pit and fissure sealant with good curing strength and effective for covering a layer of sealing material at the pits and fissures on the surface of the teeth.
[0028] 2. The raw materials of the present invention are simple to source, low in cost, have no rejection reaction, and have excellent physical and chemical properties.
[0029] 3. Through precise formula design and heating and water removal treatment process, the final pit and fissure sealant can fit tightly to the tooth surface, forming a solid protective film, effectively isolating the invasion of food residues and bacteria, and preventing the occurrence of caries; the pit and fissure sealant can maintain long-term effectiveness in daily use and reduce the risk of falling off and damage.
[0030] 4. The preparation method of the present invention is prepared by vacuum centrifugal stirring and mixing to remove the hydrolysis caused by the unstable raw material itself absorbing moisture in the environment, or the penetration of various enzymes and bacteria in the environment into the polymer, to avoid the product from absorbing moisture in the environment and hydrolysis due to improper storage, and to solve the problem of the influence of moisture on its light-curing pit and fissure sealant material, thereby promoting its curing strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Attached Figure 1 It is a comparison chart of the curing temperature curves of the samples of Example 1 and Preparation Example 3 of the present invention versus time.
[0032] Attached Figure 2 It is a comparison chart of the curing time of the samples of Example 1 and Preparation Example 3 of the present invention.
[0033] Attached Figure 3 It is a comparison chart of the compressive strength of the samples of Example 1 and Preparation Example 3 of the present invention.
[0034] Attached Figure 4 It is a comparison chart of the curing time of the sample of Example 1 of the present invention and similar products on the market.
[0035] Attached Figure 5It is a comparison chart of the compressive strength of the sample of Example 1 of the present invention and similar products on the market.
[0036] Attached Figure 6 This is a sample picture of the fast-curing light-curing pit and fissure sealant material of the present invention in a homogeneous mucus state.
[0037] Attached Figure 7 This is a sample picture of the fast-curing light-curing pit and fissure sealant material of the present invention being formed after being irradiated by a light-curing lamp.
[0038] Attached Figure 8 The figure is a comparison diagram of the fast-curing light-curing pit and fissure sealant material of the present invention before and after it is used for pit and fissure sealing of human teeth. DETAILED DESCRIPTION
[0039] The invention provides a fast-curing light-curing pit and fissure sealant material, which comprises the following components: a resin matrix material, a diluent, an inorganic filler, a light-curing initiator and an anti-hydrolysis agent.
[0040] In a fast-curing light-curing pit and fissure sealant material of the present invention, the addition of an anti-hydrolysis agent ensures that the light-curing pit and fissure sealant material has anti-hydrolysis ability on a certain basis, can significantly improve the hydrolysis resistance of the material, and extend the shelf life; at the same time, the compressive strength, hardness and bonding force of the light-curing pit and fissure sealant material can be improved, and the curing time can be significantly reduced, which has a promoting effect on improving the effect of clinical sealing, and improves the biological safety of the material and the effectiveness of clinical sealing; and the anti-hydrolysis agent is simple in source, low in cost, does not have rejection reaction, and has excellent physical and chemical properties. The resin matrix material of the present invention provides the main strength and durability of the sealant, and the diluent can improve the fluidity and processing performance of the resin; the addition of an inorganic filler can not only improve the wear resistance, compressive strength, hardness and crack resistance of the pit and fissure sealant, but also reduce the volume shrinkage of the material and improve the sealing effect; in the heating and mixing process, the inorganic filler and the resin matrix form a good combination to jointly constitute the overall structure of the pit and fissure sealant; the photocuring initiator can initiate the polymerization reaction of the resin matrix material under light. The present invention compounds resin matrix / diluent / photocuring initiator / inorganic filler / anti-hydrolysis agent components into a photocurable pit and fissure sealant material. The photocurable pit and fissure sealant material is formed after being irradiated by a photocuring lamp. Its curing time is shortened by 40% to 60%, which greatly improves its curing efficiency. It has good curing strength, compressive strength and strong bonding force, has a promoting effect on preventing the occurrence of dental caries, and improves the safety of the material and the effectiveness of dental caries prevention.
[0041] Preferably, a fast-curing light-curing pit and fissure sealant material comprises the following components, measured by mass percentage: 20% to 90% of a resin matrix material, 5% to 45% of a diluent, 1% to 30% of an inorganic filler, 0.1% to 10% of a light-curing initiator, and 0.5% to 15% of an anti-hydrolysis agent, and the total content of each component is 100%.
[0042] More preferably, a fast-curing light-curing pit and fissure sealant material comprises the following components, calculated by mass percentage: 45% to 70% of a resin matrix material, 15% to 30% of a diluent, 5% to 20% of an inorganic filler, 0.5% to 5% of a light-curing initiator, and 0.5% to 10% of an anti-hydrolysis agent, and the total content of each component is 100%.
[0043] Exemplarily, the mass percentages of the resin matrix material, the diluent, the inorganic filler, the photocuring initiator, and the anti-hydrolysis agent are 63%, 24.5%, 10%, 1%, and 1.5%, respectively.
[0044] Exemplarily, the mass percentages of the resin matrix material, the diluent, the inorganic filler, the photocuring initiator, and the anti-hydrolysis agent are 57.8%, 22%, 18%, 1.3%, and 0.9%, respectively.
[0045] Preferably, the inorganic filler is an inorganic filler that has been subjected to a heating and dehydration treatment.
[0046] The resin matrix material includes one or two of bisphenol A-glycidyl methacrylate (Bis-GMA) and diurethane dimethacrylate (UDMA) mixed in any proportion.
[0047] The diluent includes one of methyl methacrylate and triethylene glycol dimethacrylate (TEGDMA) or a mixture of the two in any proportion.
[0048] The inorganic filler includes one or more of silicon dioxide, aluminum oxide, glass powder, hydroxyapatite, diatomaceous earth, and barium silicate mixed in any proportion.
[0049] The photocuring initiator is a CQ visible light initiation reaction system, which is a mixture of at least one or more of camphorquinone, pentaerythritol tetrakis-3-mercaptopropionate (PETMP) and n-dodecyl mercaptan in any proportion.
[0050] The anti-hydrolysis agent is at least one or more of monomeric carbodiimide, polymeric carbodiimide, diphenyliodonium hexafluorophosphate, isocyanate anti-hydrolysis agent, oxazoline compound, and epoxy compound, mixed in any proportion.
[0051] The isocyanate anti-hydrolysis agent includes toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate and isophorone diisocyanate.
[0052] Preferably, in the components of a fast-curing light-curing pit and fissure sealant material, the resin matrix material is bisphenol A-glycidyl methacrylate, the diluent is triethylene glycol dimethacrylate, the light-curing initiator is camphorquinone, the anti-hydrolysis agent is diphenyliodonium hexafluorophosphate, and the inorganic filler is one or more of silicon dioxide, glass powder, diatomaceous earth, and barium silicate mixed in any proportion. More preferably, the inorganic filler is a mixture of silicon dioxide and diatomaceous earth.
[0053] Preferably, the content of the inorganic filler passing through a 300-400 mesh sieve (38-50 μm) is not less than 85%.
[0054] The present invention also provides a method for preparing a fast-curing light-curing pit and fissure sealant material, comprising the following steps:
[0055] Step (1): In a light-proof condition, the inorganic filler and the resin matrix material are heated to remove water, and the resin matrix material is heated to a molten state.
[0056] In this step (1), the raw material is heated and dried for a certain period of time to remove water, so as to remove the unstable raw material itself absorbing water from the environment and causing hydrolysis, or the various enzymes and bacteria in the environment penetrating into the polymer, affecting the curing strength.
[0057] Step (2): In a light-proof condition, the diluent, the photocuring initiator, the anti-hydrolysis agent, the dehydrated inorganic filler, and the molten resin matrix material are mixed and stirred to form a homogeneous viscous liquid, and then vacuum centrifuged and stirred to obtain a photocurable pit and fissure sealant material.
[0058] The vacuum centrifugal stirring time is 5 minutes, and the centrifugal speed is sequentially set to 900 r / min for the starting speed of 0-10S, 1000 r / min for 10-100S, 1300 r / min for 100-270S, and 900 r / min for the speed reduction of 270-300S.
[0059] The temperature for heating and dehydrating the inorganic filler and the resin matrix material is 50°C to 70°C.
[0060] The inorganic filler and the resin matrix material are heated and dehydrated in a light-proof vacuum drying oven.
[0061] The specific preparation steps of a fast-curing light-curing pit and fissure sealant material can be as follows:
[0062] Step (1): first preheat the working chamber of a light-proof vacuum drying oven to 50°C to 70°C, place the inorganic filler in a vacuum drying oven at 50°C to 70°C and heat and dry it for more than 2 hours. Preferably, the filler can be stirred at any time during the heating and drying process; loosen the mouth of the resin matrix material bottle, place it in a vacuum drying oven at 50°C to 70°C and heat and dry it for about 0.5 to 1 hour, and heat it until the resin matrix material is in a flowable viscous state (i.e., molten state) for use.
[0063] Step (2): 20% to 90% of the molten resin matrix material and 5% to 45% of the diluent are heated and stirred in a vacuum in the dark for about 0.5 to 1 hour; 1% to 30% of the inorganic filler after heating and drying is added to the mixed mucus of the diluent and the resin matrix material, heated and stirred in a vacuum in the dark for more than 2 hours, and stirred until there is no large mucus particles for use; 0.5% to 5% of the photocuring initiator is added to the mucus, and the vacuum heating and stirring is continued in the dark for about 0.5 to 1 hour, and 0.5% to 10% of the anti-hydrolysis agent is continued to be added and heated and stirred in a vacuum for about 0.5 to 1 hour, or the photocuring initiator and the anti-hydrolysis agent are added and stirred together to form a homogeneous mucus; and a vacuum centrifugal mixer is used to vacuum centrifuge and stir for about 5 minutes to obtain the light-curing pit and fissure sealant material. Then, the material can be poured and packaged.
[0064] Alternatively, step (2) may be: 20% to 90% of a molten resin matrix material, 5% to 45% of a diluent, 1% to 30% of an inorganic filler, 0.5% to 5% of a photocuring initiator, and 0.5% to 10% of an anti-hydrolysis agent are mixed together, and then heated and stirred in a vacuum environment for more than 2 hours in a dark place to form a homogeneous viscous liquid, and then stirred in a vacuum centrifugal mixer for about 5 minutes to obtain a photocurable pit and fissure sealant material.
[0065] It should be noted that during the mixing process of the vacuum centrifugal mixer, attention should be paid to the residual amount of the uniform phase mucus of the light-curing pit and fissure sealant material at all times. Do not allow air to enter the vacuum centrifugal mixer to avoid the product preparation process absorbing moisture from the environment and causing hydrolysis, which will affect the curing strength.
[0066] In the preparation process of a fast-curing light-curing pit and fissure sealant material of the present invention, the adhesive is made by vacuum heating and stirring throughout the process to isolate moisture, multiple enzymes and bacteria from penetrating into the polymer; the component raw materials are heated and dried for a certain period of time to remove water, ensuring that the raw materials are isolated from the influence of moisture; the addition of an anti-hydrolysis agent ensures that the product has anti-hydrolysis ability on a certain basis. The material source of the present invention is simple, low-cost, has no rejection reaction, and has excellent physical and chemical properties. After being irradiated by a light-curing lamp, the curing time is shortened by 40% to 60%, greatly improving its curing efficiency. The finished product has good curing strength, compressive strength and strong bonding force, which has a promoting effect on preventing the occurrence of caries, and improves the material safety and anti-caries effectiveness.
[0067] Example 1
[0068] A fast-curing light-curing pit and fissure sealant material comprises the following components: 65 g of a resin matrix material (bisphenol A-glycidyl methacrylate Bis-GMA), 25 g of a diluent (triethylene glycol dimethacrylate TEGDMA), 10 g of an inorganic filler (silicon dioxide), 1.5 g of a light-curing initiator (camphorquinone), and 1 g of an anti-hydrolysis agent (diphenyliodonium hexafluorophosphate).
[0069] The preparation steps are as follows:
[0070] (1): First, preheat the working chamber of a light-proof vacuum drying oven to 50°C to 70°C, place the inorganic filler in a vacuum drying oven at 50°C to 70°C and heat and dry it for more than 2 hours. Stir it at any time during the heating and drying process; loosen the bottle mouth of the resin matrix material, place it in a vacuum drying oven at 50°C to 70°C and heat and dry it for about 0.5 to 1 hour, and heat it until the resin matrix material becomes a flowable viscous liquid (i.e., molten state) for use.
[0071] Step (2): under light-proof conditions, heat and stir the molten resin matrix material and diluent in a vacuum-proof state for about 0.5 to 1 hour; add the inorganic filler after heating and drying to the mixed mucus of the diluent and the resin matrix material, heat and stir in a vacuum-proof state for more than 2 hours in a light-proof state, and stir until there is no large mucus particles for use; add the photocuring initiator and the anti-hydrolysis agent to the above mucus, and continue to heat and stir in a vacuum-proof state for about 0.5 to 1 hour in a light-proof state (the above diluent, the inorganic filler after heating and drying, the photocuring initiator, and the anti-hydrolysis agent can also be added to the molten resin matrix material together, and heat and stir in a vacuum-proof state for more than 2 hours in a light-proof state) to form a homogeneous mucus, and then use a vacuum centrifugal mixer to vacuum-centrifuge and stir for about 5 minutes to obtain a photocurable pit and fissure sealant material. The setting parameters of the vacuum centrifugal mixer are as follows: the vacuum centrifugal stirring time is 5 minutes, the centrifugal speed is set to 900r / min for the starting speed of 0-10S, 1000r / min for 10-100S, 1300r / min for 100-270S, and 900r / min for the speed reduction of 270-300S.
[0072] Example 2
[0073] The light-curing pit and fissure sealant material is different from that in Example 1 in that the inorganic filler silicon dioxide is 8 g, and the other components and the preparation method are the same as those in Example 1.
[0074] Example 3
[0075] The light-curing pit and fissure sealant material is different from that in Example 1 in that the inorganic filler silicon dioxide is 5 g, and the other components and the preparation method are the same as those in Example 1.
[0076] Example 4
[0077] The light-curing pit and fissure sealant material is different from that in Example 1 in that the inorganic filler silicon dioxide is 3 g, and the other components and the preparation method are the same as those in Example 1.
[0078] Example 5
[0079] The light-curing pit and fissure sealant material is different from that in Example 1 in that the inorganic filler is 10 g of glass powder, and the other components and the preparation method are the same as those in Example 1.
[0080] Example 6
[0081] The light-curing pit and fissure sealant material is different from that in Example 1 in that the inorganic filler is 10 g of diatomaceous earth, and the other components and the preparation method are the same as those in Example 1.
[0082] Example 7
[0083] The light-curing pit and fissure sealant material is different from that in Example 1 in that the inorganic filler is 10 g of barium silicate, and the other components and the preparation method are the same as those in Example 1.
[0084] Example 8
[0085] The light-curing pit and fissure sealant material is different from that in Example 1 in that the inorganic filler is a mixture of 10 g of silicon dioxide and 10 g of glass powder, and the other components and the preparation method are the same as those in Example 1.
[0086] Example 9
[0087] The light-curing pit and fissure sealant material is different from that in Example 1 in that the inorganic filler is a mixture of 10 g of silicon dioxide and 10 g of diatomaceous earth, and the other components and the preparation method are the same as those in Example 1.
[0088] Preparation Example 1
[0089] The light-curing pit and fissure sealant material comprises the following components: 65 g of resin matrix material (bisphenol A-glycidyl methacrylate Bis-GMA), 25 g of diluent (triethylene glycol dimethacrylate TEGDMA), 10 g of inorganic filler (silicon dioxide), and 1.5 g of light-curing initiator (camphorquinone).
[0090] The preparation steps are as follows: heat the resin matrix material to a molten state under light-proof conditions, add a diluent, an inorganic filler, and a photocuring initiator therein, heat and stir in a vacuum under light-proof conditions for more than 2 hours to obtain a homogeneous viscous liquid.
[0091] Preparation Example 2
[0092] The components of the photocurable pit and fissure sealant material are consistent with those in Preparation Example 1, except that the preparation steps include heating, drying and dehydrating the inorganic filler and the resin matrix material. Specifically, the working chamber of the light-proof vacuum drying oven equipment is preheated to 50°C to 70°C, the inorganic filler is placed in a 50°C to 70°C vacuum drying oven for heating and drying for more than 2 hours, the mouth of the resin matrix material bottle is unscrewed, and it is placed in a 50°C to 70°C vacuum drying oven for heating and drying for about 0.5 to 1 hour, and the resin matrix material is heated to a flowable mucus (i.e., molten state) for standby use. Afterwards, the molten resin matrix material, diluent, inorganic filler, and photocuring initiator are mixed under light-proof conditions, and heated and stirred in a light-proof vacuum for more than 2 hours to obtain a homogeneous mucus.
[0093] Preparation Example 3
[0094] The components of the light-curing pit and fissure sealant material are consistent with those of Example 1, and the difference from Example 1 is the preparation method, which does not include measures to remove water from the raw materials. The specific preparation method is as follows: heat and melt the resin matrix material under light-proof conditions, add diluent, inorganic filler, light-curing initiator, and anti-hydrolysis agent, continue to heat and stir in a vacuum in a light-proof manner for more than 2 hours to form a uniform mucus, and then use a vacuum centrifugal mixer to vacuum centrifuge and stir for about 5 minutes to obtain a light-curing pit and fissure sealant material. The setting parameters of the vacuum centrifugal mixer are consistent with those of Example 1.
[0095] The raw material compositions of Examples 1-9 and Preparation Examples 1-3 are shown in Table 1.
[0096] Table 1 Raw material composition of Examples 1-9 and Preparation Examples 1-3
[0097]
[0098] The compressive strength, curing time, light sensitivity, curing depth, uncured film thickness and appearance of the above Examples 1-9 and Preparation Examples 1-3 were tested.
[0099] The compressive strength was tested by the following method: a polytetrafluoroethylene cylindrical mold with an inner diameter of 4 mm and a height of 8 mm was used to prepare sealant specimens. Each group of at least 10 specimens was placed on a LI-500 tensile testing machine with a compression speed of 10 mm / min, and the compressive strength of each specimen was measured.
[0100] According to the test standard of Type II sealant in the pharmaceutical industry standard YY0622-2008 / ISO 6874988 "Dental resin-based pit and fissure sealants" of the People's Republic of China, the curing time, light sensitivity, curing depth, uncured film thickness and appearance of the samples were tested. The test results are shown in Table 2.
[0101] Table 2 Test results of comparative examples and embodiments
[0102]
[0103] The photocurable pit and fissure sealant materials of Preparation Examples 1 and 2 did not add the anti-hydrolysis agent diphenyliodonium hexafluorophosphate. Preparation Example 1 did not remove water from the raw materials and did not add anti-hydrolysis agents. The curing depth and uncured film thickness were unqualified, and the appearance was abnormal. The compressive strength was 14.889, which was relatively low. Preparation Example 2 took heating and dehydration measures on the inorganic filler and the resin matrix material. The product was qualified, but its curing time was 14S. It can be seen that moisture significantly affects the curing strength of the resin-based pit and fissure sealant, which can be roughly summarized into the following three categories: 1. The raw materials themselves are unstable and absorb moisture from the environment to produce hydrolysis, or various enzymes and bacteria in the environment penetrate into the polymer; 2. The product preparation process absorbs moisture from the environment to produce hydrolysis; 3. The product is improperly stored after preparation and absorbs moisture from the environment to produce hydrolysis, or various enzymes and bacteria in the environment penetrate into the polymer.
[0104] Diphenyliodonium hexafluorophosphate is added to the light-curing pit and fissure sealant material of Preparation Example 3. The difference between Example 1 and Preparation Example 3 is whether or not the raw materials are dehydrated. Preparation Example 3 does not perform heating and dehydration measures on the raw materials, while Example 1 performs heating and dehydration measures on the inorganic filler and the resin matrix material. As shown in Table 2, the curing time of Example 1 is 6S, while the curing time of Preparation Example 3 is 14S, indicating that the heating and dehydration measures can significantly improve the curing time of the pit and fissure sealant.
[0105] In both Preparation Example 3 and Preparation Example 1, no measures were taken to remove water from the raw materials. Diphenyliodonium hexafluorophosphate was added to the light-curing pit and fissure sealant material in Preparation Example 3, and its compressive strength of 31.483 was increased by more than 1 times compared with that in Preparation Example 1, and the curing time was also shortened, indicating that diphenyliodonium hexafluorophosphate can not only reduce the curing time of the pit and fissure sealant, but also significantly improve its compressive strength after curing.
[0106] Attached Figure 1 It is a comparison chart of the curing temperature curves changing with time during the curing time test process of the samples of Example 1 and Preparation Example 3 of the present invention.
[0107] Attached Figure 2 3 is a comparison chart of the curing time of the samples of Example 1 and Preparation Example 3 of the present invention. 12 groups of parallel experiments were carried out on the samples of Example 1 and Preparation Example 3. It can be seen that the curing time of Example 1 is shorter and more stable.
[0108] Attached Figure 3 3 is a comparison chart of the compressive strength of the samples of Example 1 and Preparation Example 3 of the present invention. 11 groups of parallel experiments were carried out on the samples of Example 1 and Preparation Example 3. It can be seen that the compressive strength of Example 1 is larger and more stable.
[0109] The samples of Example 1 of the present application and similar products on the market were tested for curing time and compressive strength. The test results are as follows: Figure 4 , Figure 5 shown.
[0110] Attached Figure 4 This is a comparison chart of the curing time of the sample in Example 1 of the present invention and similar products on the market at home and abroad. It can be seen that the curing time of similar products on the market is generally above 9S.
[0111] Attached Figure 5 This is a comparison chart of the compressive strength of the sample of Example 1 of the present invention and similar products on the market. It can be seen that by selecting a suitable inorganic filler, adding an anti-hydrolysis agent and performing a water removal treatment, various properties of the light-cured pit and fissure sealant are improved.
[0112] Those skilled in the art should understand that the above-mentioned specific embodiments are merely examples and not limitations, and various modifications, combinations, partial combinations and replacements may be made to the embodiments of the present invention according to design requirements and other factors. As long as they are within the scope of the attached claims or their equivalents, they are within the scope of rights to be protected by the present invention.
Claims
1. A fast-curing light-curing pit and fissure sealant material, characterized in that: The invention comprises the following components: a resin matrix material, a diluent, an inorganic filler, a photocuring initiator and an anti-hydrolysis agent.
2. The fast-curing light-curing pit and fissure sealant material according to claim 1, characterized in that: The composition includes the following components in percentage by mass: 20% to 90% of resin matrix material, 5% to 45% of diluent, 1% to 30% of inorganic filler, 0.1% to 10% of photocuring initiator and 0.5% to 15% of anti-hydrolysis agent.
3. The fast-curing light-curing pit and fissure sealant material according to claim 2, characterized in that: The composition includes the following components in percentage by mass: 45% to 70% of resin matrix material, 15% to 30% of diluent, 5% to 20% of inorganic filler, 0.5% to 5% of photocuring initiator and 0.5% to 10% of anti-hydrolysis agent.
4. The fast-curing light-curing pit and fissure sealant material according to claim 1, characterized in that: The inorganic filler is an inorganic filler that has been subjected to a heating and dehydration treatment; or / and the resin matrix material comprises one or two of bisphenol A-glycidyl methacrylate and diurethane dimethacrylate mixed in any proportion; or / and the diluent includes one or two of methyl methacrylate and triethylene glycol dimethacrylate mixed in any proportion; or / and the inorganic filler includes one or more of silicon dioxide, aluminum oxide, glass powder, hydroxyapatite, diatomaceous earth, and barium silicate mixed in any proportion; Or / and the photocuring initiator is a CQ visible light initiation reaction system, which is a mixture of at least one or more of camphorquinone, pentaerythritol tetrakis-3-mercaptopropionate, and n-dodecyl mercaptan in any proportion; Or / and the anti-hydrolysis agent is at least one or more of monomeric carbodiimide, polymeric carbodiimide, diphenyliodonium hexafluorophosphate, isocyanate anti-hydrolysis agent, oxazoline compound, epoxy compound mixed in any proportion.
5. The fast-curing light-curing pit and fissure sealant material according to claim 4, characterized in that: The resin matrix material is bisphenol A-glycidyl methacrylate, the diluent is triethylene glycol dimethacrylate, the photocuring initiator is camphorquinone, the anti-hydrolysis agent is diphenyliodonium hexafluorophosphate, and the inorganic filler is one or more of silicon dioxide, glass powder, diatomaceous earth, and barium silicate mixed in any proportion.
6. The fast-curing light-curing pit and fissure sealant material according to claim 1, characterized in that: The content of the inorganic filler passing through a 300-400 mesh sieve is not less than 85%.
7. The method for preparing a fast-curing light-curing pit and fissure sealant material according to any one of claims 1 to 6, characterized in that: The following steps are involved: In a light-proof condition, the inorganic filler and the resin matrix material are heated to remove water, and the resin matrix material is heated to a molten state; Under light-proof conditions, the diluent, photocuring initiator, anti-hydrolysis agent, dehydrated inorganic filler and molten resin matrix material are mixed and stirred to form a homogeneous viscous liquid, which is then stirred by vacuum centrifugation to obtain a photocurable pit and fissure sealant material.
8. The method for preparing a fast-curing light-curing pit and fissure sealant material according to claim 7, characterized in that: The vacuum centrifugal stirring time is 5 minutes, and the centrifugal speed is sequentially set to 900 r / min for the starting speed of 0-10S, 1000 r / min for 10-100S, 1300 r / min for 100-270S, and 900 r / min for the speed reduction of 270-300S.
9. The method for preparing a fast-curing light-curing pit and fissure sealant material according to claim 7, characterized in that: The temperature of the inorganic filler and the resin matrix material for heating and dehydration treatment is 50°C to 70°C; Or / and the inorganic filler and the resin matrix material are heated and dehydrated in a light-proof vacuum drying oven.
Citation Information
Patent Citations
Photochromic dental composite material and preparation method thereof
CN114767549A
Photocuring color-changing pit and fissure sealing agent as well as preparation method and application thereof
CN115487075A
Indicator-containing pit and fissure sealing agent as well as preparation method and application thereof
CN117017790A
Method and apparatus for recommending classical music based on user information
KR1020250140693A